(untitled) (Research, Society and Development, 2023)
Temporomandibular Disorder (TMD) is a disorder that involves the masticatory muscles, temporomandibular joint (TMJ) and associated structures. Its etiology is multifactorial and involves different aspects such as muscular, occlusal, psychological problems, structural and postural abnormalities, parafunctional habits, degenerative processes and traumatic injuries. Among the psychological consequences associated with TMD, the risk of developing anxiety and depression in patients with this clinical condition is greater in women, individuals with poor social support and patients with myofascial pain. Therefore, early diagnosis and a multidisciplinary approach are very important, where the role of the psychologist is fundamental in the correct diagnosis and monitoring for the successful treatment of these patients. Therefore, the study has the following problem: What are the psychological consequences associated with temporomandibular disorder? The general objective of the research included demonstrating the psychological aspects related to the occurrence of temporomandibular dysfunction in individuals and the specific ones were to conceptualize temporomandibular dysfunction and its rate of occurrence, expose the consequences associated with temporomandibular dysfunction and advocate the role of the Dentist in cases of temporomandibular dysfunction. An intense relationship was noticed between psychological disorders and TMD, which is worth highlighting that the occurrence of symptoms of a single disorder can lead to the appearance of others, requiring more rigorous monitoring in women who may present signs and symptoms with bigger frequency.